Upaya Diplomasi Publik Tiongkok ke ASEAN Melalui ASEAN China Young Leaders Scholarship Tahun 2022-2024 - Amanda Nazhira Firdaus; Athaya Aza Nabil Hibrizi; Septiandini Saskia Putri,; Praja Firdaus Nuryananda (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
ASEAN China Young Leaders Scholarship (ACYLS) is one form of public diplomacy effort carried out by China to establish cooperative relations in the field of education with ASEAN. This study will discuss how China's public diplomacy efforts towards ASEAN as China's strategic partner in implementing its foreign policy through the ASEAN China Young Leaders Scholarship program in 2022 to 2024. Since the beginning of diplomatic relations between China and ASEAN in 1996, both parties have actively created various kinds of cooperation to support development and economic growth in ASEAN and improve China's positive image at the international level. This article uses a qualitative method with the theoretical framework of Nicholas J. Cull to analyze the implementation of public diplomacy with the variables of listening, advocacy, and international broadcasting. From these variables, it will show how ACYLS can improve China's image among ASEAN citizens and the global public.